PENGARUH DIVERSIFIKASI DAN KEPUTUSAN PENDANAAN TERHADAP KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Suchandiko Elmayola; Efni Yulia; Rokhmawati Andewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aimed to analyze the effect of diversification and funding decisions on company performance and value of companies with Good Corporate Governance (GCG) as a moderating variabel in an industrial manufacturing company listed on Stock Exchange (BEI) in 2013-2017. Sampling method using purposive samples techniques and accuired 41 companies manufacturing industry. Samples were analyzed by using PLS. The results of this study indicated that diversification has no directly significant effect on firm value. Funding decisions has an significant effect on the value of the company. The company’s performance significantly influence the value of the company. The funding decision has an significant influence on the company’s value through indirect. Diversification has a significant influence on the company’s value through indirect. GCG has no significant effect in moderating influence funding decision on firm value. GCG has a significant effect in moderating the effect of diversification on firm value.Keywords: Diversification,Financial Decision, Financial Performance, Firm Value, Good Corporate Governance